Effectiveness of communication channels on level of awareness and determinants of adoption of improved common bean technologies among smallholder farmers in Tanzania - Lugamara, C.B.; Urassa, J.K.; Nguezet, P.M.D.; Masso, C. (Springer, 2019)
Increased legume productivity contributes to nutritional security as they are a source of cheap proteins. However, there is limited access to information on improved legume technologies among smallholder farmers in resource poor countries such as Tanzania. This chapter is aimed at assessing the effectiveness of communication channels (i.e. demonstration plots, farmer field days, technological briefs) on level of awareness and the determinants of adoption of improved common bean technologies among smallholder farmers in Tanzania. The study on which the chapter is based used a cross-sectional design on 400 households in Gairo and Mvomero districts, Tanzania. Results show that more than a half of the farmers were aware of all the seven improved legume technologies assessed. However, the level of awareness on all the technologies differed across the treatments, with a high level of the awareness recorded in areas with interventions. Among others, intervention included sharing information with farmers on land preparation, legume variety selection, use of quality seed, fertiliser application at planting, planting and spacing, weeding, control of insect and storage pests and diseases, harvesting and storage and safe use of chemicals. The awareness was low in areas without intervention. Nonetheless, there was a low level of adoption of the improved legume technologies. This could be due to the fact that the intervention was at its initial stage of implementation; but it was expected to increase with time as knowledge diffuses to the communities. In addition, as pointed out in the focus group discussions, low adoption could be because of difficulties in accessing improved bean technologies (high costs associated), unavailability of improved seeds and absence of seed dealers nearby villages. The factors significantly (p ≤ 0.05) associated with smallholder farmers’ adoption of improved legume technologies were visits by extension officers, age of household head, being member of a farmers’ association, revenue from other income-generating activities and household size. Therefore, it can be concluded that a combination of demonstration plots, farmer field days and technological briefs (leaflets and brochures) accounted for the effective communication and awareness creation. Thus, it is recommended that the government and non-governmental organisations should invest more in awareness creation approaches in order to make sure that all smallholder farmers are sensitised on the improved legume technologies. In addition, the government and non-governmental organisations should insist more on visits by extension officers, formation of/joining farmers association and participating in other income-generating activities to enhance adoption of improved legume technologies.